(3HjGf GdCSQGQ ddWGdHjf aj GdJUhas - (3GdchQGfj, jhSa Hf YHO Gddg Hf YeQ, J(B768(3g`s ((3MGLj Hf EHQGgje Hf Ydj GdJQGHjs)
(3ChdgG (B:s
(3GdMeO ddg GdbGOQ GdYdjehHYO aGdYde CTQa efbHI CeG HYO adeG Ndb Gddg QhM eMeO Ydjg GdSdGe ChdGs
(3BNQgG (B:s
(3ajaQ ef bHQg Edi dWag hjaQ efg Edjg eJPddG eJVQYG eJedbG eYJPQG eYJQaG HPfhHg aj HGHg ajJhbY ajV GdWGbI hQMeJg Ydi PfhHg Cf Gddg gh GdHQ GdQMje hGdLhGO GdcQjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 240s
(3eYLe GdeDdajf(B: 4 / 169s
(3cTa GdXfhf(B: 1 / 260s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs